Glucose Syrup from Purple Sweet Potatoes (Ipomoea batatas L. Poir) using Acid Hydrolysis Method - Esa Nur Shohih; Dendi Sri Sulistyantoro; Vira Mawardha Putri (Program studi Teknik Kimia UNS, 2024)
Abstract. The making of glucose syrup from purple sweet potatoes is motivated by the high demand for alternative sugar in Indonesia. Through the processes that have been carried out and the results of previous studies, the potential of purple sweet potatoes to be processed into glucose syrup has been produced. This experiment was conducted to determine whether purple sweet potatoes can be processed into glucose syrup and to determine the suitability of the product to the standard. To convert purple sweet potatoes into glucose syrup, it is necessary to first extract the starch content in purple sweet potatoes and go through the process of making glucose syrup by the acid hydrolysis method using citric acid of various concentrations (0.2, 0.4, 0.6, 1 N). For the feasibility of consuming glucose syrup from purple sweet potatoes, a toxicity test was carried out using the Brine Shrimp Lethality Test (BSLT) method. Tests were also carried out on water, ash, reducing sugar, and starch content to then be compared with the Indonesian glucose syrup standard (SNI 01-2978-1992). The results showed that the reducing sugar content of purple sweet potato glucose syrup followed the glucose syrup quality standard, which was 43.31%, the lowest water content was 18.35%, the lowest ash content was 7.95% and there was no starch content in purple sweet potato liquid sugar. The aroma of the glucose syrup produced was following the Indonesian National Standard, but the color and taste produced were not yet in accordance. The toxicity test of purple sweet potato liquid sugar showed a lethal concentration value of LC50 >1,000 ppm, which means that purple sweet potato liquid sugar has no toxic potential so it is safe for consumption.Keywords:Purple Sweet Potatoes, Liquid Sugar, Acid Hydrolysis